Semiotik ikon, indeks, simbol Analisis Semiotik Film Pariban Karya Agustinus Sitorus: Analisis Semiotik Film Pariban Karya Agustinus Sitorus - Tonggina Angel Yana; Ahada Wahyusari; Siti Habiba; Harry Andheska; Dody Irawan; Tessa Dwi Leoni (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research discusses the semiotic types of the film Pariban by Agustinus Sitorus based on the object of study in the form of a film which contains semiotic types in the form of icons, indices and symbols. The aim of this research is to describe the icons, indices and symbols in the film Pariban by Agustinus Sitorus. The method used in this research is qualitative descriptive research. The data collection techniques used to obtain data are listening, observing, recording and transferring data. In analyzing data, the techniques used are Selecting data, Grouping data, Analyzing data, Interpreting data, Concluding data. After that draw conclusions from the data obtained. The results of this research obtained semiotic types in the form of icons, indices and symbols.